2007
DOI: 10.1542/peds.2006-2614
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Directly Observed Therapy for HIV-Infected Children and Adolescents to Assess Adherence to Antiretroviral Medications

Abstract: BACKGROUND. The introduction of highly active antiretroviral therapy for HIV led to significant declines in HIV-associated morbidity and mortality in children. Nonadherence to antiretroviral therapy is the leading cause of treatment failure in HIV-infected patients. The ability to recognize nonadherence is suboptimal, and differentiating it from other causes of inadequate viral suppression may be difficult. OBJECTIVES. The purpose of this work was to examine the efficacy of hospital-based direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
1
20
0
6
Order By: Relevance
“…Our data, Glikman et al (2007), and Parsons et al (2006) demonstrated that measuring viral loads with DOT can provide valuable information about a patient's response to ARV treatment. These results also demonstrate that heavily treatment-experienced patients can experience a virologic response with DOT and without a change in regimen.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 57%
See 2 more Smart Citations
“…Our data, Glikman et al (2007), and Parsons et al (2006) demonstrated that measuring viral loads with DOT can provide valuable information about a patient's response to ARV treatment. These results also demonstrate that heavily treatment-experienced patients can experience a virologic response with DOT and without a change in regimen.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 57%
“…Recent reports have demonstrated that using medical institution-based DOT can improve adherence and virologic and immunologic responses (Glikman, Walsh, Valkenburg, Mangat, & Marcinak, 2007;Parsons et al, 2006). In these studies, children and adolescents (mean age of 13 years [range, 7-17 years] and 12.6 years [range, 0.8-16 years], respectively) with perinatally-acquired HIV were admitted to the hospital for non-adherence concerns and received DOT for all ARV doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Published DOT experience in youth is limited but promising and is primarily from inpatient and clinic-based settings. [13][14][15] DOT is resource intensive and before designing large-scale studies to assess DOT efficacy and associated behavior change among nonadherent youth, the feasibility and acceptability of this potentially intrusive intervention were assessed. Here, we describe the results of a pilot study to examine DOT feasibility in nonadherent youth with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term hospitalizations in the era of cART have been successfully utilized to assess cART adherence and work on strategies to improve motivation and self-effi cacy of antiretroviral medication adherence. Hospital-based directly observed therapy can be considered for patients with severe immune-compromise and poor virologic control in whom all outpatient interventions have been unsuccessful [42].…”
Section: Provision Of Clinical Carementioning
confidence: 99%